Psychological correlates of performance in elite female basketball players. - Lukins, J.; Leicht, A.; Spinks, W. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
Basketball is a fast-paced court sport currently played by over 100,000 females in Australia. Despite this popularity and the presence of a national competition since 1980, research into the sporting experience of elite female basketball players is limited. 19 elite female basketball players competing in the Women`s National Basketball League (WNBL) participated in this research. A pre-screening questionnaire, the Sport Competition Anxiety Test (SCAT), and the Task-Ego Orientation in Sport Questionnaire were completed prior to the commencement of the 2002-3 season. During the season, players completed the Profile of Mood States (POMS) 1-hour prior to each game Performance data was recorded for each player for each game. Results indicated that tension was significantly correlated with anger ( =.67, p<.05), and depression ( =.80, p<.01). Those participants with lower levels of fatigue ( =-.64, p<.05) and anger ( =-.87, p<.01) had a significantly higher free throw percentage. Those players who were more successful in converting free throw shots made significantly more personal fouls ( =.81, p<.01), thus suggesting higher involvement with the game. Interestingly significant differences were not found for home and away games on mood states such as anger (F(1 ,48) = .63, p = ..43), vigour (F(1 ,48) = .04, p = 85.), and fatigue (F(1 ,48) = 1.21, p = .277). Implications for the findings of this research may have practical application for coaches and players. Suggestions will be offered for further development of this research with female athletes.